Impact of Monetary Policy Shocks on Macroeconomic Fundamentals: The Role of Asymmetry and Uncertainty in Nigeria - Deekor, LeeLee N. (Advances in Social Sciences Research Journal, 2019)
That monetary policy is made in an environment of substantial uncertainty is only a commonplace knowledge. But for the peculiar vulnerability of monetary authorities to exogenous conditions in developing economies, we hypothesized for the role of uncertainty in the asymmetry effect of monetary policy. Essentially, we explore both money supply and interest rate process using linear and non-linear ARDL to show that political pressure such as variability in government borrowing has the potential to accelerate the asymmetry effect of monetary policy. We also observe the asymmetry effect of monetary policy to be sensitive to the choice of monetary policy indicator. These findings suggest that monetary authorities must consider not only the effectiveness or otherwise of monetary policy instruments to affect the target policy goals, but also the fact that not all the target variables react in a similar way to expansionary and contractionary monetary policy shocks.